Perbandingan Efektivitas Google Ads dan Meta Business Ads dalam Meningkatkan Lead Produk CRM di PT Ciptadra Softindo - Adiyat, Afghan Hanif; Kasih, Jemiro; Panji, Krisna (LPPM STT Terpadu Nurul Fikri, 2025)
PT Ciptadra Softindo utilizes two major advertising platforms—Meta Business Ads and Google Ads—in parallel to promote its Onebox CRM product. However, there has been no systematic evaluation of the relative effectiveness of each platform in generating high-quality leads within the B2B sector. This study aims to analyze and compare the effectiveness of both platforms in increasing the quantity and quality of leads for the Onebox CRM product. The research was conducted over a three-month period, measuring ten key performance parameters: impression, click-through rate (CTR), cost per click (CPC), link clicks, number of incoming leads, relevant leads, qualified leads ratio, spam rate, conversion rate, and cost per lead (CPL). A quantitative method was employed using a controlled experimental approach, with statistical testing performed via independent samples t-test using GraphPad Prism software to compare campaign performance metrics. The results indicate that Meta Business Ads significantly outperformed Google Ads across most conversion-related parameters, particularly in the number of relevant leads, conversion rate, and cost efficiency (CPL). Meanwhile, Google Ads demonstrated stronger performance in awareness-oriented metrics such as CTR and link clicks, making it more suitable for the product awareness stage within search engine environments. This study concludes that Meta Business Ads is a more effective and efficient advertising platform for generating B2B conversion leads for CRM products in the context of PT Ciptadra Softindo’s market.